An orientalist "Journey" to Istanbul From the super bowl final: The shifting of classical orientalist discourse - Nizam, Feridun (IGI Global, 2021)
This study is firstly built on the determination of the orientalist elements in Turkish Airlines' commercial film Journey, which was broadcast in the Super Bowl final of the 2019 American Football League, and how Turkish culture is represented in Istanbul with these orientalist elements. In the context of the sample handled in the study, Turkish architectural structures, Turkish historical structures, Turkish Islamic cultural elements, and Turkish traditions are included, and the presentation of Istanbul from the eyes of a "foreigner" with an orientalist point of view has been handled with the method of semiotic analysis. The main problem of the study is on the different presentation of the East and Istanbul, despite the usual orientalist perspective in media contents and especially in advertising. In this sense, it focuses not on antiorientalism, but on the conclusion that orientalism is presented with the change of classical narratives. © 2021, IGI Global.